Nanowire-doped positive electrode material as well as preparation method and application thereof

By doping metal oxide nano wires in positive materials, the problem of poor performance in the process of charging and discharge in the charging process of the ternary orthopedic material is solved, and the effect of improving the efficiency, magnification and cycle performance of the first circle, and simplifying the preparation process , Suitable for industrial production.

CN119330421APending Publication Date: 2025-01-21JINGMEN GEM NEW MATERIAL CO LTD +1

Patent Information

Application Number
CN202411457351.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

During the charging and discharging process, the existing ternary positive electrode materials have problems such as low first-round efficiency, poor cycle performance, and unsatisfactory rate performance, and the preparation method is complex and not suitable for industrial mass production.

Method used

The cathode material is doped with metal oxide nanowires, and the cathode material doped with nanowires is prepared by mixing the cathode precursor, lithium source and metal oxide nanowires and calcining them.

Benefits of technology

It significantly improves the diffusion rate of lithium ions in the electrode solid and electrolyte/electrode interface, buffers the volume change of the electrode material during charge and discharge, maintains the stability of the electrode material structure, improves the electrochemical performance, and is suitable for industrial mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330421A_ABST
    Figure CN119330421A_ABST
Patent Text Reader

Abstract

The invention discloses a nanowire-doped positive electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: mixing a positive electrode precursor, a lithium source and a metal oxide nanowire, and calcining to obtain the nanowire-doped positive electrode material. According to the invention, the metal oxide nanowire is used for doping the positive electrode material, and the introduction of the metal oxide nanowire avoids side reaction between the material surface and electrolyte, inhibits surface and interface structure degradation, relieves mechanical stress at the interface, reduces the possibility of cracking, and is beneficial to improving the structure and thermal stability of the material. Moreover, doping of the metal oxide nanowires does not hinder Li ion transmission, the material has relatively low internal resistance and is beneficial to maintaining good rate capability, and the first-circle efficiency, the rate capability and the cycle performance of the nanowire-doped positive electrode material prepared by the method disclosed by the invention are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries and relates to a nanowire-doped positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of new energy vehicles, lithium battery technology has become more mature, and people have higher and higher requirements for the battery life. This requires the battery cell to have a higher energy density and the battery cell material to exert a higher capacity. The ideal positive electrode material must have the following characteristics: (1) The presence of transition metal ions with high redox potential and easy redox, ensuring that the lithium-ion battery has a high charge and discharge capacity and open circuit voltage; (2) Good lithium ion and electron conductivity, providing excellent rate performance; (3) Good safety, with high chemical stability and thermodynamic stability; (4) Easy to prepare, environmentally friendly, and cheap.

[0003] Ternary materials have good electrochemical properties, are easy to prepare, and are environmentally friendly, and are currently the focus of research in the industry. However, the cycle performance and rate performance of nickel-cobalt-manganese ternary materials have not been very ideal, especially high-nickel positive electrode materials, which have low first-cycle efficiency during the charge and discharge process, and the stable layered structure is transformed into an unstable rock salt structure during the charge and discharge process, resulting in poor cycle performance. In addition, problems such as cation mixing, poor thermal stability, and microcracks have greatly limited the practical application of nickel-rich ternary materials.

[0004] For the above defects of ternary cathode materials, the general modification methods are mainly element doping and surface coating. Element doping is mainly metal cation and fluoride anion doping, which can enhance the structural stability of the material to a certain extent, but there is a problem of uneven doping. The doping elements are distributed on the surface and bulk of the material particles, which is easy to form a mixed phase. Moreover, element doping cannot solve the problem of oxygen evolution of the material under high voltage.

[0005] The preparation methods of ternary materials mainly include solid phase method and co-precipitation method. Although the traditional solid phase method is simple in process, it is difficult to prepare ternary materials with controllable morphology, uniform particle size and stable electrochemical performance because it only uses simple mechanical mixing; in order to obtain uniform hydroxide precipitation, the co-precipitation method requires strict control of experimental conditions such as raw material concentration, dropwise addition speed, stirring speed, pH value and reaction temperature. The method is complicated and the primary particles of the prepared microspheres are closely stacked, resulting in the inability to fully infiltrate the electrolyte and increase the diffusion path of lithium ions, which seriously affects the capacity and rate performance of the electrode material.

[0006] CN112993258B discloses a doping and coating method for ternary positive electrode materials, ternary positive electrode materials and lithium ion batteries, the method comprising: 1) using silicate, doped metal source, nickel source, cobalt source and manganese source, a one-step coprecipitation method to prepare a ternary positive electrode material precursor, sintering once to obtain a ternary positive electrode material core co-doped with silicon and doped metal elements; 2) using a saturated solution of silicate as a base liquid to clean the ternary positive electrode material core, adding metal salts during the cleaning process for precipitation and coating, dehydrating and sintering twice to obtain the doped and coated ternary positive electrode material. The positive electrode material prepared by this method has good doping and coating effects, can effectively solve the gas production problem, and improve the cycle performance.

[0007] CN112701271A discloses an element doping method based on a ternary precursor positive electrode material, the steps of which include: weighing a soluble nickel salt, a soluble cobalt salt and a soluble manganese salt and dissolving them in deionized water to obtain a ternary metal salt solution; preparing an alkaline complexing agent, mixing the alkaline complexing agent with the ternary metal salt solution for reaction, and then collecting, filtering, washing and drying in sequence to obtain a ternary precursor powder; preparing a doping element salt solution, mixing the ternary precursor powder with the doping element salt solution and performing a liquid phase diffusion reaction, and drying to obtain a doped precursor powder; mixing the doping precursor powder with lithium hydroxide powder uniformly and then calcining to obtain a doped ternary positive electrode material. The present invention adopts a liquid phase diffusion method to infiltrate the doping element into the voids of the ternary precursor through a solvent, significantly improving the overall doping content and doping uniformity.

[0008] However, the above method is cumbersome to operate and is not suitable for industrial mass production. Therefore, there is an urgent need in the art to provide a simple preparation method for positive electrode materials to effectively improve the first cycle efficiency, rate performance and cycle performance of positive electrode materials, so as to facilitate industrial promotion and application. Summary of the invention

[0009] In view of the above technical problems existing in the prior art, the object of the present invention is to provide a nanowire-doped positive electrode material and a preparation method and application thereof.

[0010] To achieve the above object, the present invention adopts the following technical solutions:

[0011] In a first aspect, the present invention provides a method for preparing a nanowire-doped positive electrode material, the preparation method comprising the following steps:

[0012] The positive electrode precursor, the lithium source and the metal oxide nanowires are mixed and calcined to obtain the nanowire-doped positive electrode material.

[0013] The present invention can significantly improve the diffusion rate of lithium ions in the electrode solid and the electrolyte / electrode interface by doping the positive electrode material with metal oxide nanowires, and can effectively buffer the large volume change of the electrode material during the charge and discharge cycle, maintain the stability of the electrode material structure, and improve its electrochemical performance. At the same time, the introduction of metal oxide nanowires avoids side reactions between the material surface and the electrolyte, inhibits the degradation of the surface interface structure, relieves the mechanical stress at the interface, reduces the possibility of cracking, and is conducive to improving the structure and thermal stability of the material. In addition, the doping of metal oxide nanowires will not hinder the transmission of Li ions, and the material has a lower internal resistance, which is conducive to maintaining good rate performance. The first-cycle efficiency, rate performance and cycle performance of the nanowire-doped positive electrode material prepared by the method of the present invention are improved.

[0014] The process of the invention is simple, has few processes, and is suitable for batch production.

[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0016] Preferably, the metal oxide nanowires are one or more of aluminum oxide nanowires, titanium oxide nanowires, magnesium oxide nanowires, zirconium oxide nanowires, cobalt oxide nanowires, zinc oxide nanowires, and strontium oxide nanowires.

[0017] Preferably, the diameter of the nanowire is 10 nm to 25 nm, for example, 10 nm, 12 nm, 14 nm, 15 nm, 16 nm, 18 nm, 20 nm, 21 nm, 23 nm or 25 nm, etc. If metal oxide nanowires with too large a diameter are used for doping, the electrochemical performance of the material will decrease, because the overly thick metal oxide nanowires cannot fill the pores on the surface of the positive electrode material particles, and cannot effectively reduce the contact area between the electrode and the electrolyte to inhibit the occurrence of side reactions, thereby failing to improve the material's capacitance, rate performance and cycle performance.

[0018] Preferably, the length of the nanowire is 7μm to 15μm, for example, it can be 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or 15μm, etc.

[0019] The one-dimensional nanowire material has a large specific surface area. As a doping material, within the above diameter and length range, the metal oxide nanowire can fill the pores on the surface of the positive electrode material particles, greatly reducing the contact area between the electrode and the electrolyte. After high-temperature calcination, the nanowire particles and the positive electrode material (such as ternary materials) are more firmly composited, and the residual alkali (such as Li2O) on the surface is eliminated, the alkalinity is reduced, thereby inhibiting the occurrence of side reactions, which is conducive to improving the electrochemical performance of the positive electrode material.

[0020] Preferably, the metal oxide nanowires are prepared by electrospinning. The preparation of metal oxide nanowires by electrospinning is a prior art, and those skilled in the art can prepare them by referring to the methods disclosed in the prior art, which will not be described in detail here.

[0021] Preferably, the amount of the metal oxide nanowires satisfies: the molar percentage of the metal element in the positive electrode precursor is 0.1% to 0.5%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4% or 0.5%. The appropriate amount of metal doping helps to stably improve the electrochemical performance of the material. The doping element can expand the plane spacing of the material lattice without destroying its original layered structure. When the metal doping amount is low, it cannot effectively enhance the stability of the material structure and improve the rate performance. A high doping amount will affect the energy density of the positive electrode material, increase the impedance of the material and thus affect its performance.

[0022] Preferably, the particle size D50 of the positive electrode precursor is 3 μm to 5 μm, for example, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm.

[0023] Preferably, the molar ratio of the positive electrode precursor to the lithium source is 1:(1.02-1.07), for example, it can be 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06 or 1:1.07.

[0024] Preferably, the calcination temperature is 800°C to 1000°C, for example, it may be 800°C, 825°C, 850°C, 870°C, 880°C, 900°C, 925°C, 950°C, 975°C or 1000°C.

[0025] Preferably, the calcination time is 10 h to 12 h, for example, 10 h, 10.5 h, 11 h, 11.5 h or 12 h.

[0026] The present invention does not impose any particular limitation on the equipment used for calcination, and it may be, for example, a tubular furnace.

[0027] Preferably, the cathode precursor is a ternary precursor.

[0028] Preferably, the method for preparing the cathode precursor comprises the following steps: adding a metal salt solution, a complexing agent solution and a precipitant solution into a reaction kettle in parallel, and performing a coprecipitation reaction under the protection of a protective gas to obtain a cathode precursor.

[0029] In a second aspect, the present invention provides a nanowire-doped positive electrode material, wherein the nanowire-doped positive electrode material is prepared by the method described in the first aspect.

[0030] In a third aspect, the present invention provides a lithium-ion battery, comprising the nanowire-doped positive electrode material according to the second aspect.

[0031] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention dopes the positive electrode material with metal oxide nanowires. The introduction of metal oxide nanowires avoids side reactions between the material surface and the electrolyte, inhibits surface interface structure degradation, relieves mechanical stress at the interface, reduces the possibility of cracking, and is beneficial to improving the structure and thermal stability of the material. In addition, the doping of metal oxide nanowires will not hinder the transmission of Li ions, and the material has a lower internal resistance, which is beneficial to maintaining good rate performance. The first-cycle efficiency, rate performance and cycle performance of the nanowire-doped positive electrode material prepared by the method of the present invention are improved.

[0034] (2) The process of the present invention is simple, has few processes, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 SEM image of the nanowire-doped ternary cathode material prepared in Example 1. DETAILED DESCRIPTION

[0036] The technical solution of the present invention is further described below with reference to the accompanying drawings and through specific implementation methods.

[0037] The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0038] Example 1

[0039] This embodiment provides a method for preparing a nanowire-doped ternary cathode material, comprising the following steps:

[0040] 1. Dissolve nickel sulfate, cobalt sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Co:Mn=8:1:1 to obtain a 3 mol / L nickel-cobalt-manganese mixed metal salt solution;

[0041] 2. Add 120L of pure water to a 200L reactor, control the temperature to 58°C, control the stirring speed to 380rpm, introduce sodium hydroxide solution and ammonia solution to adjust the pH value to 11.30±0.10 to obtain a bottom liquid, continuously introduce nitrogen into the reactor, and introduce the nickel-cobalt-manganese mixed metal salt solution (with a constant flow rate), sodium hydroxide solution and ammonia solution prepared in step (1) into the bottom liquid of the reactor in parallel. After the reaction starts, adjust the flow rate of the sodium hydroxide solution to gradually reduce the pH value in the reactor to 11.10±0.10, and control the flow rate of the ammonia solution so that the ammonia concentration in the reactor is within the range of 5-8g / L; when the D50 of the reaction slurry in the reactor reaches 3.5±0.2μm, stop the reactor, wash, filter and remove iron from the slurry to obtain an undoped ternary precursor.

[0042] 3. The precursor prepared in step 2 is mixed evenly with lithium hydroxide and aluminum oxide nanowires (diameter 20 nm, length 10 μm) prepared by electrospinning to obtain a mixed material; wherein the molar ratio of the precursor to lithium hydroxide is 1:1.05, and the molar percentage of aluminum in the precursor is 0.2%.

[0043] 4. The mixed material in step 5 was sintered in a tube furnace at 900° C. for 10 h to obtain a nanowire-doped ternary positive electrode material.

[0044] Figure 1 The SEM image of the nanowire-doped ternary cathode material prepared in this embodiment shows that the doped nanowire particles are clearly visible and evenly distributed on the surface of the ternary cathode material without changing the original structure of the ternary cathode material.

[0045] Example 2

[0046] This embodiment provides a method for preparing a nanowire-doped ternary cathode material, comprising the following steps:

[0047] 1. Dissolve nickel chloride, cobalt chloride and manganese chloride in deionized water at a molar ratio of Ni:Co:Mn=6:1:3 to obtain a 2 mol / L nickel-cobalt-manganese mixed metal salt solution;

[0048] 2. Add 120L of pure water to a 200L reactor, control the temperature to 65°C, control the stirring speed to 300rpm, introduce sodium hydroxide solution and ammonia solution to adjust the pH value to 11.60±0.10 to obtain a bottom liquid, continue to introduce helium into the reactor, and introduce the nickel-cobalt-manganese mixed metal salt solution (constant flow rate), sodium hydroxide solution and ammonia solution prepared in step (1) into the bottom liquid of the reactor in parallel. After the reaction starts, adjust the flow rate of the sodium hydroxide solution to gradually reduce the pH value in the reactor to 11.30±0.10, and control the flow rate of the ammonia solution so that the ammonia concentration in the reactor is 7g / L; when the D50 of the reaction slurry in the reactor reaches 4.0±0.2μm, stop the machine, wash, filter and remove iron from the slurry to obtain an undoped ternary precursor.

[0049] 3. The precursor prepared in step 2 is mixed evenly with lithium carbonate and titanium oxide nanowires (diameter 15 nm, length 15 μm) prepared by electrospinning to obtain a mixed material; wherein the molar ratio of the precursor to lithium hydroxide is 1:1.03, and the molar percentage of titanium in the precursor is 0.3%.

[0050] 4. The mixed material in step 5 was sintered in a tube furnace at 800°C for 12 h to obtain a nanowire-doped ternary positive electrode material.

[0051] Example 3

[0052] This embodiment provides a method for preparing a nanowire-doped ternary cathode material, comprising the following steps:

[0053] 1. Dissolve nickel sulfate, cobalt sulfate and manganese sulfate in deionized water at a molar ratio of Ni:Co:Mn=8:1:1 to obtain a 3 mol / L nickel-cobalt-manganese mixed metal salt solution;

[0054] 2. Add 120L of pure water to a 200L reactor, control the temperature to 55°C, control the stirring speed to 400rpm, introduce sodium hydroxide solution and ammonia solution to adjust the pH value to 11.80±0.10 to obtain a bottom liquid, continuously introduce nitrogen into the reactor, and introduce the nickel-cobalt-manganese mixed metal salt solution (with a constant flow rate), sodium hydroxide solution and ammonia solution prepared in step (1) into the bottom liquid of the reactor in parallel. After the reaction starts, adjust the flow rate of the sodium hydroxide solution to gradually reduce the pH value in the reactor to 11.50±0.10, and control the flow rate of the ammonia solution so that the ammonia concentration in the reactor is 6g / L; when the D50 of the reaction slurry in the reactor reaches 4.5±0.2μm, stop the machine, wash, filter and remove iron from the slurry to obtain an undoped ternary precursor.

[0055] 3. The precursor prepared in step 2 is mixed evenly with lithium hydroxide, and aluminum oxide and titanium oxide nanowires (both with a diameter of 25 nm and a length of 11 μm) prepared by electrospinning to obtain a mixed material; wherein the molar ratio of the precursor to lithium hydroxide is 1:1.04, and the molar percentage of aluminum and titanium in the precursor is 0.05%.

[0056] 4. The mixed material in step 5 was sintered in a tube furnace at 1000° C. for 10 h to obtain a nanowire-doped ternary positive electrode material.

[0057] Example 4

[0058] The difference between this embodiment and embodiment 1 is that the molar percentage of aluminum in the precursor is 0.05%.

[0059] Example 5

[0060] The difference between this embodiment and embodiment 1 is that the molar percentage of aluminum in the precursor is 5.5%.

[0061] Example 6

[0062] The difference between this embodiment and embodiment 1 is that the diameter of the aluminum oxide nanowires is 30 nm.

[0063] Example 7

[0064] The difference between this embodiment and embodiment 1 is that the length of the aluminum oxide nanowires is 6 μm.

[0065] Example 8

[0066] The difference between this embodiment and embodiment 1 is that the length of the aluminum oxide nanowires is 16 μm.

[0067] Comparative Example 1

[0068] The difference between Comparative Example 1 and Example 1 is that the aluminum oxide has spherical particles and a particle size D50 of 10 μm.

[0069] Preparation of positive electrode sheet: The positive electrode materials provided in Examples 1-8 and Comparative Example 1 were mixed with conductive carbon black SP (purchased from TIMCAL) and polyvinylidene fluoride PVDF (brand HSV900) in a mass ratio of 90:5:5 for positive electrode material, SP and PVDF, and N-methylpyrrolidone was used as solvent. The mixed and stirred into slurry, and the obtained slurry was evenly coated on aluminum foil with a scraper with a coating gap of 100 μm. After coating, it was first dried at 120°C by blast drying, then rolled, and finally the dried electrode sheet was cut into Φ12 circular electrode sheets, and vacuum dried at 120°C to obtain the positive electrode sheet of button half-cell.

[0070] The negative electrode is a Φ14 metal lithium sheet, the separator is a Φ19 PP microporous membrane (Celgard2400), and the electrolyte is a lithium battery basic electrolyte, that is, EC and DEC are used as a mixed solvent in a volume ratio of 1:1, and 1.1 mol / L LiPF6 is added. The positive electrode sheet, metal lithium sheet, separator and electrolyte are assembled to obtain a button battery.

[0071] Performance Testing:

[0072] (1) First cycle efficiency test: at 0.1C (1C = 180mAg -1 ) to 4.3V;

[0073] (2) Rate performance test: Charge and discharge cycle tests were performed at 0.1C, 0.2C, 0.5C, 1C, 2C and 5C respectively. After 5 cycles at each rate, the test was returned to 0.1C. The capacity retention rate was calculated based on the capacity loss, and the rate performance was compared.

[0074] (3) Cycle performance test: A charge and discharge test was performed at 1C, and the material capacity after 100 cycles was statistically analyzed to obtain the cycle capacity retention rate.

[0075] See Table 1 for the results.

[0076] Table 1

[0077]

[0078] As can be seen from Table 1, the present invention can effectively improve the first cycle efficiency, rate performance and cycle capacity retention rate of the positive electrode material prepared by doping the positive electrode material with metal oxide nanowires.

[0079] By comparing Example 1 with Examples 4-5, it can be seen that a suitable amount of metal doping helps to stably improve the electrochemical properties of the material. The doping elements can expand the plane spacing of the material lattice without destroying its original layered structure. When the metal doping amount is too low, it cannot effectively enhance the stability of the material structure and improve the rate performance. A high doping amount will affect the energy density of the positive electrode material, increase the impedance of the material and thus affect its performance.

[0080] By comparing Examples 1 and 6, it can be seen that if metal oxide nanowires with a diameter that is too large are used for doping in the present invention, the electrochemical performance of the material decreases. This is because the overly thick metal oxide nanowires cannot fill the pores on the surface of the positive electrode material particles, cannot effectively reduce the contact area between the electrode and the electrolyte to inhibit the occurrence of side reactions, and thus cannot improve the material's capacitance, rate performance and cycle performance.

[0081] By comparing Example 1 with Examples 7-8, it can be seen that the length of the metal nanowires will also affect the performance of the material. If the metal nanowires are too long, the specific capacity of the positive electrode material will be too low. If they are too short, the conductivity of the material will not be significantly improved, and the internal resistance of the material will be large, which is not conducive to the capacity and other electrochemical properties. After high-temperature calcination, the nanowire material of appropriate length can be more firmly composited with the ternary oxide, and can also eliminate residual Li2O on the surface, reduce alkalinity, thereby inhibiting the occurrence of side reactions and improving the electrochemical performance of the material.

[0082] By comparing Example 1 with Comparative Example 1, it can be seen that if non-nanowire spherical metal oxides are used for doping, the capacitance, rate performance and cycle performance of the material cannot be significantly improved. The one-dimensional structure of the metal nanowire material gives it a large specific surface area. As a doping material, the constructed conductive network system can significantly increase the diffusion rate of lithium ions in the electrode solid and the electrolyte / electrode interface, and can effectively buffer the large volume change of the electrode material during the charge and discharge cycle, maintain the stability of the electrode material structure, and improve its electrochemical performance.

[0083] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a nanowire-doped positive electrode material, characterized in that: The preparation method comprises the following steps: The positive electrode precursor, the lithium source and the metal oxide nanowires are mixed and calcined to obtain the nanowire-doped positive electrode material.

2. The preparation method according to claim 1, characterized in that: The metal oxide nanowires are one or more of aluminum oxide nanowires, titanium oxide nanowires, magnesium oxide nanowires, zirconium oxide nanowires, cobalt oxide nanowires, zinc oxide nanowires or strontium oxide nanowires; Preferably, the diameter of the nanowire is 10 nm to 25 nm; Preferably, the length of the nanowire is 7 μm to 15 μm.

3. The preparation method according to claim 1 or 2, characterized in that: The metal oxide nanowires are metal oxide nanowires prepared by electrostatic spinning.

4. The preparation method according to any one of claims 1 to 3, characterized in that The amount of the metal oxide nanowires used satisfies that the molar percentage of the metal element in the positive electrode precursor is 0.1% to 0.5%.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The particle size D50 of the positive electrode precursor is 3 μm to 5 μm.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The molar ratio of the positive electrode precursor to the lithium source is 1:(1.02-1.07).

7. The preparation method according to any one of claims 1 to 6, characterized in that: The calcination temperature is 800°C to 1000°C; Preferably, the calcination time is 10 h to 12 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The cathode precursor is a ternary precursor; Preferably, the method for preparing the cathode precursor comprises the following steps: adding a metal salt solution, a complexing agent solution and a precipitant solution into a reaction kettle in parallel, and performing a coprecipitation reaction under the protection of a protective gas to obtain a cathode precursor.

9. A nanowire-doped positive electrode material, characterized in that: The nanowire-doped positive electrode material is prepared by the method according to any one of claims 1 to 8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the nanowire-doped positive electrode material of claim 9.

Citation Information

Patent Citations

  • Element doping method based on ternary precursor positive electrode material

    CN112701271A

  • Doping and coating methods for ternary cathode materials, ternary cathode materials and lithium-ion batteries

    CN112993258B

Cited By

  • Three-dimensional graphene nanowire composite doped precursor, positive electrode material and preparation method

    CN120681752A